Characteristics of Solid Soap from Used Cooking Oil and Kalamansi Orange Peel Essential Oil - Marliza, Bella; Olivia, Reza; Sari, Aplina Kartika; Mualim (BIOEDUSCIENCE, 2026)
Background: Used cooking oil is defined as cooking oil that has been used for frying more than three times. Consuming used cooking oil poses serious health risks because it can cause several diseases and its waste can damage the environment. The purpose of this study was to determine the characteristics of foam height, pH, and organoleptic tests on solid soap made from used cooking oil with calamansi orange peel essential oil. Methods: This study was quasi-experimental using one liter of used cooking oil as a sample. Analysis was carried out univariately. Results: Based on the research results, the color, aroma, and shape of solid soap made from used cooking oil passed the organoleptic test and met the requirements of SNI 06 3532 1994. The average pH test results showed a pH value of 9, which met the SNI 06 3532 1994 standard. The results of the test on the foam height of solid soap from used cooking oil showed an average foam height of 5.91, which did not meet the SNI 06 3532 1994 standard. Conclusions: The results of this study aim to provide information to the public about the method of processing unused used cooking oil into more useful materials and increase economic value